Simulation and experimental research on droplet flow characteristics and deposition in airflow field - Xiahou, Bing; Sun, Daozong; Song, Shuran; Xue, Xiuyun; Dai, Qiufang (International Journal of Agricultural and Biological Engineering, 2020)
In order to study the motion law of droplet flow under the airflow action of long-range air-blast sprayers, a CFD-based 3D model was established for the air-blast sprayer duct and its external airflow field, and the discrete phase model was introduced to simulate the motion of droplet flow in the airflow. The simulation data of the droplet flow trajectory, droplet flow parameters and droplet deposition were obtained by establishing the monitoring sections and bilateral coupling calculation in the airflow field. Results showed that gravity had an obvious effect on droplets and large droplets settled faster. Some of the larger droplets were formed by polymerization in droplets motion. The smaller droplets were transported further along with the airflow, and the long-range sprayer has a significant effect on the directional transport of small droplets. Besides, the spraying swath in the direction perpendicular to the range enlarged gradually with the increase of the spraying range. At the end of the range, the diffuse and drifting of the droplets were dominant. Given that the outlet airflow velocity of the sprayer duct was 25.01 m/s and the spray pressure 1.8 MPa, the maximum motion distances of aerosol, mist, fine mist and coarse mist in the airflow field were 18.5 m, 19.5 m, 17.5 m and 10.5 m, respectively. Droplet size and number as well as number density and volume density of droplet flow on all monitoring sections showed a regression function with changes in the distance of the spraying range. The simulation results of the model adopted in this paper were verified by Chi-square test between the simulation results of the droplet deposition and the spray measurement results. Research results provide a new method for the study of orchard air-blast spraying technology and references for the optimization of spraying technology.Keywords: droplet flow, droplet density, air-blast sprayer, computational fluid dynamics, droplet depositionDOI: 10.25165/j.ijabe.20201306.5455Citation: Xiahou B, Sun D Z, Song S R, Xue X Y, Dai Q F. Simulation and experimental research on droplet flow characteristics and deposition in airflow field. Int J Agric & Biol Eng, 2020; 13(6): 16–24.